Responsabilidade social corporativa como estratégia de negócio: modelos conceituais e exemplos ilustrativos - Leite, Lilian Christiane Quarezemin Corrêa (2011)
The Corporate Social Responsibility theme has been gaining strength and attention from the corporations as well as from the civil society. The impacts of the post WWII world, globalization and development stack pollution as well as environmental and social consequences. As actors inserted in this reality, corporations also suffer the consequences of theses changes. The very role of corporations in society and the limits and reach of its attention gather new perspectives. The current conjuncture brings corporations new challenges and possibilities in the field of Corporate Responsibility. These changes have impact on the organization itself (it's goals, relationship with consumers, employees, etc.) and, as a consequence, on its strategies. Great part of Corporate Responsibility actions are based on a very narrow field – essentially a reactive posture, as a result of pressure and obligation. Nonetheless, a new approach has been on the rise, a more proactive stance: in some pioneer companies, Corporate Responsibility is viewed as a fundamental and integral part of the company strategy, generating benefits not only for society, but for the company as well. This paper initiates with an investigation on the literature on the evolution of Social Responsibility. After that, it proposes a conceptual model explaining the relationship between Corporate Reponsibility and Strategy, which exposes possible routes of integration between them. Starting from the idea that Corporate Responsibility can be approached as a strategic question capable of suficing, in different fathoms and levels, crucial points for good corporate performance. The applicability of the proposed model is demonstrated through the analysis illustrative examples of companies that have been incorporating Corporate Responsibility as an important part of its business strategy. As a conclusion, it can be deduced that when it becomes part of a formal strategy, the adoption of a responsible approach not only brings image gains, but it also generates, for the companies that practice it, tangible results, while ate the same time assuring for society a more sustainable world, with improved quality of life for everyone.